Public food procurement as a game changer for food system transformation - Swensson, Luana; Hunter, Danny; Tartanac, Florence; Schneider, Sergio (Elsevier, 2021)
The last decade has seen various countries, regions, and cities from low-income to high-income economies develop public food procurement (PFP) initiatives designed to use government purchasing power and regular demand for food as a policy instrument to promote sustainable development. These initiatives—often also referred to as institutional food procurement, including school meals programmes and purchase of food for public hospitals, prisons, universities, public building cafeterias, and other social programmes— have been increasingly recognised as an important entry point to trigger more sustainable food systems and healthy diets. They are also an important instrument for the achievement of target 12.7 of the UN Sustainable Development Goals (SDGs): “to promote public procurement practices that are sustainable in accordance with national policies and priorities”.